Austentatious : The Evolving World of Jane Austen Fans - Luetkenhaus, Holly, 1985-; Weinstein, Zoe, 1990- (Book collections on Project MUSE., 2019)
"The amount of fan-generated content about Jane Austen and her novels has long surpassed the author's original canon. Adaptations like Clueless, Pride and Prejudice and Zombies, Jane Austen's Fight Club, and The Lizzie Bennet Diaries have given Austen fans priceless opportunities to enjoy the classic texts anew, and continue to bring new and younger fans into the fold. Now, with the accessibility of modern technology and the ability to connect with other fans in an instant online, the amount and type of fan-created works has exponentially multiplied in recent years. Fans write stories, create art, make videos, and craft memes, all in homage to one of the most celebrated authors of all time. This book explores online fan spaces in search of "Janeites" all over the world to discover what fans are making, how fans are sharing their work, and why it matters that so many women and nonbinary individuals find a haven, not only in Jane Austen, but also in Jane Austen fandom"--